Drug-Coated Balloon for the Treatment of Femoropopliteal Tosaka Class III In-stent Restenosis Lesions - Zhang, Bihui; Niu, Guochen; Yan, Ziguang; Zou, Yinghua; Tong, Xiaoqiang; Yang, Min (Frontiers in Surgery, 2021)
Background: There is little evidence of effectiveness and safety of DCB in treating Tosaka class Ⅲ in-stent restenosis (ISR) lesions in real world. The aim of this study was to investigate the clinical effectiveness and safety of DCB in real-world Tosaka class Ⅲ ISR femoropopliteal lesions. Methods: The single-center study enrolled 28 femoropopliteal ISR Tosaka Ⅲ patients treated by DCB from September 2016 to September 2018. Patency, freedom from target lesion revascularization (TLR) rate, clinical improvement, and safety endpoints were analyzed for 14-month follow-up. Results: Of the patients, 32.1% had critical limb ischemia. Mean lesion length was 250.4 ± 93.9 mm. Technical success was achieved in all lesions (100%). Debulking devices were used in 50% of lesions. Bailout stent was performed in 3.6%. Kaplan Meier estimate of 14-month primary patency was 79.2% (95%CI 60.6% to 97.8%), whereas freedom from TLR was 91.5% (95%CI 80.1% to 100%). Symptoms improved by at least 1 Rutherford category in 82.1% of limbs. Ankle-brachial index (ABI) values improved from 0.51± 0.30 to 1.05± 0.22 at final follow up (P<0.001). Freedom from 30-day major adverse limb events (MALE) was 100%. The mortality rate was 3.6% Conclusion: These results suggest that the use of DCB is safe and effective in treating femoropopliteal Tosaka class Ⅲ ISR lesions.